Implementation of K-12 state standards for mathematics and English language arts and literacy : findings from the American teacher panel - Opfer, V. Darleen; Kaufman, Julia H.; Thompson, Lindsey E. (Research report (Rand Corporation), 2016)
This report examines teachers’ implementation of new, more-rigorous K–12 state standards for mathematics and English language arts and literacy, including use of instructional materials, perceptions about content and approaches aligned with standards, and student engagement with standards. Results are intended to help states or districts reflect upon areas where teachers may benefit from guidance about how to address their state standards.